Understanding the role played by parents, culture and the school curriculum in socializing young women on sexual health issues in rural South African communities - Feziwe Mpondo; Robert A.C. Ruiter; Dilana Schaafsma; Bart van den Borne; Priscilla S. Reddy (Taylor & Francis Group, 2018)
Background: the decline in South Africa's HIV infection rates especially among young women is encouraging. However, studies show that the 15-24-year-old cohort remains vulnerable. As they still report early sexual debut, being involved in sexual partnerships with older men as well as having unprotected sex. These risky sexual behaviors may be linked to factors such as the parent-child sexual health communication and the timing of the first talk. The quality of sexual health information received in school may also be important for enhancing healthier sexual behaviors. Aims and Objectives: to investigate the what, when and how sexual health communication occurs in rural South African families and to determine whether such communication patterns have changed over time. We also wanted to get an in-depth understanding of the roles played by culture, sexual health education and peers in the socialization of young women on sexual matters. Methods: a purposive sample of (n = 55) women who were 18-35 years old was selected and interviewed in focus group discussions (FGDs). Results: the FGD findings show that parent-child communication on sexual matters in rural communities is limited to messages that warn against pregnancy. It is also laden with cultural idioms that are not well explained. The school sexual health curriculum also fails to adequately equip adolescents to make informed decisions regarding sexual matters. All this seems to leave room for reception of misguided information from peers. Conclusions: findings highlight a need for designing interventions that can create awareness for parents on the current developmental needs and sexual behavior of adolescents. For adolescents programs would need to focus on providing skills on personal responsibility, and how to change behavior to enhance sexual health.